Bioink Formulations for Bone Tissue Regeneration - Li, Na; Guo, Rui; Zhang, Zhenyu Jason (Frontiers in Bioengineering and Biotechnology, 2021)
Unlike conventional techniques used to generate porous scaffolds, three-dimensional (3D) bioprinting technology enables fabrication of scaffolds with complex and diverse geometry, which facilitate evenly distributed cells and orderly release of signal factors. To date, a range of cell-laden materials, such as natural or synthetic polymers, and ceramics, has been deployed by the 3D bioprinting technique to construct complex scaffold systems and regenerate substitutes for the natural extracellular matrix (ECM). Four-dimensional (4D) bioprinting technology has attracted much attention because it can compensate for the dynamic structural and functional transformations of scaffolds that cannot be achieved by 3D bioprinting. However, there remain challenges with the formulation, commonly known as bioink, to meet the technical requirements in terms of appropriate processability of the bioink, desired mechanical properties of the hydrogel implants, and cell-guided functionality of biomaterials. Recent bioprinting techniques are reviewed in this article, discussing strategies for hydrogel-based bioinks to mimic native bone tissue-like extracellular matrix environment, including properties of bioink formulation required for bioprinting, structure requirements, and biological evaluation, and preparation of tough hydrogel scaffolds. Stimulus mechanisms that are commonly used to trigger the dynamic structural and functional transformations of the scaffold are analyzed. At the end, we highlighted the current challenges and possible avenues of smart hydrogel-based bioink/scaffolds for bone tissue regeneration.